Ujaran Kebencian (Hate Speech) dalam Konteks Pemilihan Umum - Pilander, Marsheila Carla; Lolong, Wenly Ronald Jefferson; Rawung, Hendrasari (Fakultas Ilmu Sosial dan Hukum, 2024)
This study examines the regulation of hate speech crimes in elections in Indonesia, focusing on the mechanism of action against such crimes. The type of research used is normative legal research using a legislative approach. The results of the study show that although there are laws and regulations, there is no consensus on what is meant by hate speech in elections, which causes law enforcement to be inconsistent and ineffective. The mechanism for dealing with hate speech includes campaign supervision, public reports, investigations, decision-making, sanctions, and further legal processes. Clarity in hate speech regulations is essential for effective and fair law enforcement.